Comparison of Clinical and Hemodynamic Effects of Isoflurane and Sevoflurane Anesthesia in Calves - Yaygingul, Rahime; Belge, Ali; Akin, Ibrahim; Unsal, Cengiz; Bulut, Osman; Kilic, Nuh (Acta Scientiae Veterinariae, 2017)
Background: Inhalation anesthesia is the preferred method for use on many animal species, including ruminants, due to its superiority over the injectable anesthetics. The most commonly used inhalation anesthetics are isoflurane and sevoflurane The aim of the study was to investigate the effects of isoflurane and sevoflurane anesthesia on the cardiovascular system of calves. Materials, Methods & Results: A total of 20 calves (11 male, 9 female) between 1 and 6 months in age and 50 to 85 kg in body weight were used. The calves were divided randomly into two groups of 10 each, with one group being administered isoflurane and the other sevoflurane. An intramuscular dosage of 0.1 mg/kg of xylazine was administered to the calves as premedication. Induction was performed 10 min after calves were given an intramuscular dosage of 4 mg/kg of ketamine. Inhalation anesthesia was maintained with isoflurane or sevoflurane in 100% oxygen saturation. Before anesthesia, after induction and at intervals of 5, 10, 15, 20, 25, 30, 45, and 60 min of anesthesia, the body temperature, heart rate, and respiratory rate of the calves were recorded. Additionally, before anesthesia, after induction and at intervals of 15, 30, 45, and 60 min of anesthesia, serum electrolyte (Na+, Ca++, K+, Mg++) and blood gases (pH, pCO2, pO2, HCO3-, TCO2, O2Sat, HCT) were evaluated from blood samples taken from both groups. The second derivation, durations and amplitudes of the P and T waves, the durations and amplitudes of the QRS complex, and the durations of PQ and QT intervals were evaluated on the ECGs recorded before anesthesia, after induction and during anesthesia. Following anesthesia termination, the extubation time and the time it took for straightening of the head and standing up were recorded. Decrease in heart rate and body temperature were found significant in two of the groups. Decrease in respiratory rate compared to initial values after premedication was statistically significant for both groups. However, during anesthesia, an increase occurred. This incresae in respiration rate was not statistically significant compared to initial values. The incease in the values of pCO2, pO2, HCO3 and the decrease in the values of pH and Hct comparing the initial values was found statistically significant in both groups. Discussion: In ruminants, isoflurane has an induction concentration of 3-5% and an anesthetic concentration of 1.5-3%, while sevoflurane has an induction concentration of 4-6% and an anesthetic concentration of 2.5-4%. In this study, the concentration of isoflurane was 2.3% (2-5) and the of sevoflurane was 4.07% (3-5) for surgery. In the isoflurane group, extubation, straightening of the head and standing up times were 12.40 ± 3.77 min, 20.4 ± 1.57 min, and 30.80 ± 1.89 min, respectively. In the sevoflurane group, extubation, straightening of the head and standing up times were 13.40 ± 4.99, 19.2 ± 1.49, and 28.0 ± 1.83 min, respectively. Although the calves in the isoflurane group were extubated earlier than those of the sevoflurane group, the time elapsed for straightening of the head and standing up were longer than that of the sevoflurane group. The anesthesia protocol provided a smooth anesthetic administration, general anesthesia and awakening. In conclusion, the effects of isoflurane and sevoflurane anesthesia on the cardiovascular and respiratory system were similar, and although the changes that emerged during anesthesia were statistically significant, it was nonetheless found that the changes were within the physiological limits.